Combined inhibition of MEK and Aurora A kinase in KRAS/PIK3CA double-mutant colorectal cancer models - Davis, S. Lindsey; Robertson, Kelli M.; Pitts, Todd M.; Tentler, John J.; Bradshaw-Pierce, Erica L.; Klauck, Peter J.; Bagby, Stacey M.; Hyatt, Stephanie L.; Selby, Heather M.; Spreafico, Anna; Ecsedy, Jeffrey A.; Arcaroli, John J.; et al. (Frontiers in Pharmacology, 2015)
Aurora A kinase and MEK inhibitors induce different, and potentially complementary, effects on the cell cycle of malignant cells, suggesting a rational basis for utilizing these agents in combination. In this work, the combination of an Aurora A kinase and MEK inhibitor was evaluated in pre-clinical colorectal cancer models, with a focus on identifying a subpopulation in which it might be most effective. Increased synergistic activity of the drug combination was identified in colorectal cancer cell lines with concomitant KRAS and PIK3CA mutations. Anti-proliferative effects were observed upon treatment of these double-mutant cell lines with the drug combination, and tumor growth inhibition was observed in double-mutant human tumor xenografts, though effects were variable within this subset. Additional evaluation suggests that degree of G2/M delay and p53 mutation status affect apoptotic activity induced by combination therapy with an Aurora A kinase and MEK inhibitor in KRAS and PIK3CA mutant colorectal cancer. Overall, in vitro and in vivo testing was unable to identify a subset of colorectal cancer that was consistently responsive to the combination of a MEK and Aurora A kinase inhibitor.